TLR4/NF-κB Signaling Induces GSDMD-Related Pyroptosis in Tubular Cells in Diabetic Kidney Disease - Wang, Youliang; Zhu, Xuejing; Yuan, Shuguang; Wen, Si; Liu, Xuemei; Wang, Chang; Qu, Zhong; Li, Jun; Liu, Hong; Sun, Lin; Liu, Fuyou (Frontiers in Endocrinology, 2019)
Gasdermin D (GSDMD) has been proved to be a key protein in the activation of pyroptosis. Pyroptosis of renal tubular epithelial cells contributes to the progression of tubular injury in kidney diseases. However, it remains elusive whether and how GSDMD involves in the regulation of diabetic kidney disease (DKD). In this study, we found that tubular injury is accompanied by the up-regulation of Toll-like receptor 4 (TLR4) and GSDMD in patients with diabetic kidney disease. In addition, we discovered that the expressions of cleaved Caspase-1, active N-terminal fragment of GSDMD (GSDMD-NT), IL-18 and the secretion of IL-1β also increased in the kidneys of db/db mice. These changes were partially ameliorated following intraperitoneal injection of TAK-242, an inhibitor of TLR4. Similar results were observed in human tubular cells（HK-2）subjected to high-glucose (HG) conditions and treated with TAK-242 or parthenolide (inhibitor of NF-κB) by Western blot, Enzyme-linked immunosorbent assay (ELISA) and flow cytometry. These results indicated that TLR4/NF-κB signaling could induce GSDMD-mediated pyroptosis in tubular cells in DKD.